Chronic Endometritis in Terms of the Results ofiIn Vitro Fertilization Programs (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The frequency of cholecystectomy in unsuccessful pregnancies in the IVF and PE program is 51.8%, of which 81.3% are patients with tuboperitoneal factor infertility. The sensitivity and specificity of anamnestic risk factors are compared with the data of hysteroscopic examination with separate diagnostic curettage and histological examination of the contents of the uterine cavity as methods of examination of CE in combination with ultrasound diagnostic methods and tubular biopsy of the uterine cavity. . The microbial landscape of the uterine cavity in patients with a history of unsuccessful pregnancy in the IVF and ET program against the background of cholecystectomy is mainly represented by associations of opportunistic microorganisms and viruses. However, in the group of patients with a history of implantation failure in the IVF program, bacterial contamination in the uterine cavity and in the cervical canal (p = 0.091) was 5.6% and 1.5%, respectively. it was 48.6% and 16.4% (p < 0.001). Based on the microbial landscape of the uterine cavity, the state of the receptor apparatus, the thickness of the endometrium and the state of blood flow in the endometrial vessels, the algorithm of recommended medical actions in patients with implantation failure in IVF. In the background of cholecystectomy, the program allows to increase the effectiveness of subsequent ART programs.